2023
DOI: 10.3389/fgene.2022.1087294
|View full text |Cite
|
Sign up to set email alerts
|

A disease-related essential protein prediction model based on the transfer neural network

Abstract: Essential proteins play important roles in the development and survival of organisms whose mutations are proven to be the drivers of common internal diseases having higher prevalence rates. Due to high costs of traditional biological experiments, an improved Transfer Neural Network (TNN) was designed to extract raw features from multiple biological information of proteins first, and then, based on the newly-constructed Transfer Neural Network, a novel computational model called TNNM was designed to infer essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A host of studies [ 109 , 110 , 111 , 112 , 113 ] have demonstrated the potential of these methodologies to enhance our understanding of PPI mechanisms and to develop predictive models with superior accuracy. A summary of recent research can be seen in Table 9 .…”
Section: Transfer Learning For Protein–protein Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A host of studies [ 109 , 110 , 111 , 112 , 113 ] have demonstrated the potential of these methodologies to enhance our understanding of PPI mechanisms and to develop predictive models with superior accuracy. A summary of recent research can be seen in Table 9 .…”
Section: Transfer Learning For Protein–protein Interactionsmentioning
confidence: 99%
“…Among these, Chen et al [ 109 ] put forward TNNM, a transfer neural-network-based model specifically designed for the prediction of essential proteins. The researchers achieved this by extracting raw features from multiple biological data sources and demonstrating enhanced prediction performance compared to existing models.…”
Section: Transfer Learning For Protein–protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation